1990
DOI: 10.1152/ajpgi.1990.259.2.g191
|View full text |Cite
|
Sign up to set email alerts
|

Luminal CCK-releasing factors in the isolated vascularly perfused rat duodenojejunum

Abstract: The factors operating at the apical side of the endocrine cell releasing cholecystokinin (CCK) were investigated using the isolated vascularly perfused rat duodenojejunum. In the protease-free intestinal segment, a 30-min infusion of glucose (280 mM), oleic acid (100 mM), or triglycerides containing short- or long-chain fatty acids did not alter significantly the basal level of portal CCK-like immunoreactivity (CCK-LI), while octanoic acid (100 mM) produced a transient rise of plasma CCK-LI to approximately 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 0 publications
0
35
0
3
Order By: Relevance
“…The peptide molecular weight distribution of peptones was previously determined and showed a majority (75%) of peptides with molecular size comprised between 120 and 1,200 Da and 5% of peptides with molecular size over 5,000 Da; the rest (20%) were free amino acids (14). Cell culture reagents were from Invitrogen (Cergy Pontoise,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide molecular weight distribution of peptones was previously determined and showed a majority (75%) of peptides with molecular size comprised between 120 and 1,200 Da and 5% of peptides with molecular size over 5,000 Da; the rest (20%) were free amino acids (14). Cell culture reagents were from Invitrogen (Cergy Pontoise,…”
Section: Methodsmentioning
confidence: 99%
“…peptones), which have been reported as a representative model of * The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S. the intestinal luminal dietary protein content (14), stimulated CCK gene transcription in the STC-1 enteroendocrine cell line, whereas intact proteins or free amino acids had no effect (15). The in vitro model allowed us to identify, in the CCK gene promoter, a DNA cis-element that was required for the transcriptional response to protein hydrolysates (16).…”
mentioning
confidence: 99%
“…[12][13][14] Some intact or partially digested proteins (peptone) exert strong stimulatory effects on CCK and other released satiety hormones and may therefore be applicable as functional food components to prevent over-eating. 15) Cuber et al 16) found that peptones, and not whole protein, carbohydrates or fats were strong stimulants of CCK release in the isolated rat duodenojejunum. Cordier-Bussat et al 11) have also proved that peptones directly stimulated CCK secretion in STC-1 cells.…”
mentioning
confidence: 99%
“…Parmi les acides aminés, le tryptophane et la phénylalanine sont les meilleurs sécrétagogues au moins chez le chien (Chang et Chey, 1983). Chez le rat, les protéines (Liddle et al, 1986) et les hydrolysats protéiques (Cuber et al, 1989e) …”
Section: Personnelle)unclassified
“…Les (Cuber et al, 1989a (Hopman ef al, 1985;Liddle et al, 1985;Miazza et al, 1985) et chez le chien (Fried et al, 1983;Shiratori et al, 1986) alors que seul un acide gras à chaîne courte (acide octanoïque) est capable d'induire une sécrétion transitoire de CCK chez le rat (Cuber et al, 1989e (Cuber et al, 1989c) et le gastric inhibitory polypeptide (Cuber et al, communication …”
unclassified